Is the Continuity of Islamic Banking Usage Related to Customer Religiosity? - Rahmat Dahlan; Eko Susanto; Ahmad Fauzi; Muhamad Fauzi (IAIN Syekh Nurjati Cirebon, 2025)
Performance is an indicator of the results of achieving a person's work targets in carrying out a job as a whole during a certain period in carrying out tasks that are compared with various possibilities, such as work result standards, targets or objectives or criteria that have been determined in advance and have been agreed upon together. This study aims to reconstruct the component of religiosity as one of the main factors for Muslims in muamalah, while trying to analyze the relationship between the religiosity of Islamic banking customers and the intention to continue using Islamic banking. This happens because of the tight competition in the Islamic financial industry in Indonesia, but the Islamic banking industry still has a small percentage of loyal customers, thus contributing to a low market share of Islamic banking in Indonesia. Therefore, banks need to develop strategies, such as maximizing the religiosity factor to increase the intention to continue using Islamic banking. This research was quantitative with a survey method, using a structural equation model (SEM-AMOS) to achieve research objectives. Furthermore, this study selected Islamic banking customers as samples, reaching 530 samples through convenience sampling techniques. The results demonstrated the development of novel indicator to measure individual religiosity related to economic activities. Religiosity is self-awareness of the importance of religion that shows an attitude of surrender to God. This means that a person's religiosity shows more about the processes of internalizing religious values ​​, which then unite within the individual to form daily behavior. Furthermore, this research model also reports that religiosity can significantly increase the intention to continue using Islamic banking.